Strengthening reporting of neonatal trials - Webbe, James; Ami, Baba; Butcher, Nancy J.; Rodrigues, Craig; Stallwood, Emma; Goren, Katherine; Monsour, Andrea; S. M. Chang, Alvin; Trivedi, Amit; Manley, Brett J.; McCall, Emma; Bogossian, Fiona; et al. (NLM (Medline), 2023)
BACKGROUND AND OBJECTIVES: There is variability in the selection and reporting of outcomes in neonatal abstract trials with key information frequently omitted. This can impact applicability of trial findings to clinicians, families, and caregivers, and impair evidence synthesis. The Neonatal Core Outcomes Set describes outcomes agreed as clinically important that should be assessed in all neonatal trials, and Consolidated Standards of Reporting Trials (CONSORT)-Outcomes 2022 is a new, harmonized, evidence-based reporting guideline for trial outcomes. We reviewed published trials using CONSORTOutcomes 2022 guidance to identify exemplars of neonatal core outcome reporting to strengthen description of outcomes in future trial publications. METHODS: Neonatal trials including >100 participants per arm published between 2015 to 2020 with a primary outcome included in the Neonatal Core Outcome Set were identified. Primary outcome reporting was reviewed using CONSORT 2010 and CONSORT-Outcomes 2022 guidelines by assessors recruited from Cochrane Neonatal. Examples of clear and complete outcome reporting were identified with verbatim text extracted from trial reports. RESULTS: Thirty-six trials were reviewed by 39 assessors. Examples of good reporting for CONSORT 2010 and CONSORT-Outcomes 2022 criteria were identified and subdivided into 3 outcome categories: “survival,” “short-term neonatal complications,” and “long-term developmental outcomes” depending on the core outcomes to which they relate. These examples are presented to strengthen future research reporting. CONCLUSIONS: We have identified examples of good trial outcome reporting. These illustrate how important neonatal outcomes should be reported to meet the CONSORT 2010 and CONSORTOutcomes 2022 guidelines. Emulating these examples will improve the transmission of information relating to outcomes and reduce associated research waste